2011
DOI: 10.5194/nhess-11-965-2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of ULF electromagnetic phenomena associated with the 2000 Izu Islands earthquake swarm by wavelet transform analysis

Abstract: There have been many reports on ULF electromagnetic phenomena associated with the 2000 Izu Islands earthquake swarm. In this study, seismo-magnetic anomalies are presented by examining energy variations of signatures at the periods around 100 s. Geomagnetic data observed at three stations in Izu Peninsula from 1 January 2000 to 30 April 2001 have been analyzed and wavelet transform has been performed. In order to indentify anomalous changes from ionosphere disturbances, Kakioka station has been chosen as a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…In particular, the main frequency found in the analysed ULF seismomagnetic is around 0.01 Hz, a period of 100 s; however, this main frequency can change depending on the direction, the distance, and the magnitude of each EQ analysed (Chavez et al 2011). Similar periods of the ULF seismo-magnetic phenomena have been reported by Hayakawa et al (1996), Uyeda et al (2002), Hattori (2004), Hattori, Han, Yoshino, et al (2013), Hattori, Han, and Huang (2013), and Han et al (2011Han et al ( , 2014. …”
Section: St-music-based Geomagnetic Wave Analysissupporting
confidence: 67%
“…In particular, the main frequency found in the analysed ULF seismomagnetic is around 0.01 Hz, a period of 100 s; however, this main frequency can change depending on the direction, the distance, and the magnitude of each EQ analysed (Chavez et al 2011). Similar periods of the ULF seismo-magnetic phenomena have been reported by Hayakawa et al (1996), Uyeda et al (2002), Hattori (2004), Hattori, Han, Yoshino, et al (2013), Hattori, Han, and Huang (2013), and Han et al (2011Han et al ( , 2014. …”
Section: St-music-based Geomagnetic Wave Analysissupporting
confidence: 67%
“…Recognition of anomalous pre-earthquake phenomena has been reported for major earthquakes since 1990 (Fraser-Smith et al, 1990;Bernardi et al, 1991;Molchanov et al, 1992;Kopytenko et al, 1993;Lin and Zeng, 1992;Hayakawa et al, , 1999Hayakawa et al, , 2000Kawate et al, 1998;Gotoh et al, 2002;Hattori et al, 2002Hattori et al, , 2004aHattori, 2004;Liu et al, 2006;Molchanov and Hayakawa, 2008;Chen et al, , 2011Han et al, 2011;Wen et al, 2012). These reports indicate that geomagnetic anomalies prior to earthquakes are caused by either momentary existence of earthquake-related high conductivity materials or the movement of electric current along faults (Zeng et al, 1995;Merzer and Klemperer, 1997;Yen et al, 2004).…”
Section: Introductionmentioning
confidence: 88%
“…Hattori, et al [4] reported that the best frequency to observe seismogenic activity is 0.01 Hz. This was supported by Hirano and Hattori [15] and Han, et al [16] who studied earthquakes in the Izu and Baso Peninsulas during the year of 2000 using a periodogram to analyze the magnetometer network with a sampling rate of 50 Hz. They also found that a spectrum frequency similar to the one stated above to be a suitable frequency to analyze the polarization ratio to indicate anomalous ULF emissions.…”
Section: Relevant Methods In Previous Researchesmentioning
confidence: 99%
“…Other research that also used the spectrum frequency in a similar range, below 0.1 Hz, was conducted by Hattori, et al [20]. Hattori, et al [21][22] and Han, et al [16] also reported anomalies associated with the seismogenic ULF emission spectrum to be at f = 0.01 Hz, based on research executed on the Izu and Baso Peninsulas in the Kanto region of Japan.…”
Section: Relevant Methods In Previous Researchesmentioning
confidence: 99%